DESLOCAMENTO DE ABOMASO À ESQUERDA EM VACA JERSEY: RELATO DE CASO - Lorenzatto, Deividi Valter; Cecatto, Indiamara; Parise, Sabrina; Daneluz, Marina Oliveira; Carneiro, Maico Fernando Wilges; Ansilieiro, Willian Jonas (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.